Immediate effects of the trunk stabilizing exercise on static balance parameters in double-leg and one-leg stances - Kim, Jwa-jun (J Phys Ther Sci, 2016)
[Purpose] The purpose of this study was to evaluate the immediate effect of stabilizing exercise using the PNF technique on standing balance in one-leg and double-leg stances. [Subjects and Methods] The present study recruited 34 healthy participants from a local university. The Participants performed four balance tests (double-leg stance with and without vision, one-leg stance with and without vision), before and after exercise. The exercise consisted of exercises performed using PNF techniques (stabilizing reversal and rhythmic stabilization), which were applied to facilitate trunk musculature. To examine balance ability, total displacement of the center of pressure was measured during balance tests. [Results] The total anterior–posterior center of pressure displacement was significantly reduced after applying rhythmic stabilization compared before exercise regardless of the balance test conditions. [Conclusion] The present results suggest that trunk stability exercise using rhythmic stabilization could effectively enhance balance ability under one-leg and double-leg conditions.